Benefits of Adaptive Signal Processing in a Commercially Available Cochlear Implant Sound Processor. Issue 7 (August 2015) - Wolfe, Jace; Neumann, Sara; Marsh, Megan; Schafer, Erin; Lianos, Leslie; Gilden, Jan; O'Neill, Lori; Arkis, Pete; Menapace, Christine; Nel, Esti; Jones, Marian
<x xml:space="preserve">Abstract</x> Objective Cochlear implant recipients often experience difficulty understanding speech in noise. The primary objective of this study was to evaluate the potential improvement in speech recognition in noise provided by an adaptive, commercially available sound processor that performs acoustic scene classification and automatically adjusts input signal processing to maximize performance in noise. Research Design Within-subjects, repeated-measures design. Setting This multicenter study was conducted across five sites in the U.S.A. and Australia. Patients Ninety-three adults and children with Nucleus Freedom, CI422, and CI512 cochlear implants. Intervention Subjects (previous users of the Nucleus 5 sound processor) were fitted with the Nucleus 6 sound processor. Performance was assessed while these subjects used each sound processor in the manufacturer's recommended default program (standard directionality, ASC + ADRO for the Nucleus 5 processor and ASC + ADRO and SNR-NR with SCAN for the Nucleus 6 sound processor). The subjects were also evaluated with the Nucleus 6 with standard directionality, ASC + ADRO and SNR-NR enabled but SCAN disabled. Main Outcome Measures Speech recognition in noise was assessed with AzBio sentences. Results Sentence recognition in noise was significantly better with the Nucleus 6 sound processor when used with the default input processing (ASC + ADRO, SNR-NR, and SCAN) compared to performance with the Nucleus 5 sound processor and default input processing (standard directionality, ASC + ADRO). Specifically, use of the Nucleus 6 at default settings resulted in a mean improvement in sentence recognition in noise of 27 percentage points relative to performance with the Nucleus 5 sound processor. Use of the Nucleus 6 sound processor using standard directionality, ASC + ADRO and SNR-NR (SCAN disabled) resulted in a mean improvement of 9 percentage points in sentence recognition in noise compared to performance with the Nucleus 5. Conclusion The results of this study suggest that the Nucleus 6 sound processor with acoustic scene classification, automatic, adaptive directionality, and speech enhancement in noise processing provides significantly better speech recognition in noise when compared to performance with the Nucleus 5 processor.